Dynamic proprioceptive training improves functional recovery in sprinters with patellofemoral pain: A randomized trial - Devadharshini B; Shenbaga Sundaram Subramanian; Jeevarathinam Thirumalai; Hadeel R. Bakhsh; Saad Suleman Alfawaz; Rayan Jastania; Riziq Allah Mustafa Gaowgzeh; Thamer A. Altaim; Fadwa Alhalaiqa; Porkodi Arjunan; Yasmeen Imtiaz G (PLoS ONE, 2026)
Background Patellofemoral pain syndrome (PFPS) is a common musculoskeletal condition among physically active individuals, particularly sprinters, and is frequently associated with pain, impaired balance, and reduced functional performance. This study compared the effects of dynamic proprioceptive training and conventional strengthening on multidomain functional recovery in recreational sprinters with PFPS. Methods A two-arm, assessor-blinded randomized controlled trial was conducted among 60 recreational sprinters with unilateral PFPS. Participants were randomly allocated to either a Dynamic Proprioceptive Training (DPT) group or a Strengthening Program (SP) group (n = 30 each). Both groups received supervised rehabilitation three times weekly for 12 weeks. Primary outcomes included pain intensity (Numeric Pain Rating Scale [NPRS]), dynamic balance (Y-Balance Test [YBT]), and single-hop distance. Secondary outcomes included limb symmetry index (LSI), recovery rates, and a composite Recovery Efficiency Index (REI). Assessments were performed at baseline, 6 weeks, and 12 weeks. Repeated-measures ANOVA and regression-based analyses were performed. This trial was registered with the Clinical Trials Registry of India (CTRI/2025/07/090253). Results Both groups improved significantly over time (p < 0.001). However, the DPT group demonstrated greater clinically meaningful improvements than the SP group. At 12 weeks, between-group differences favored DPT for pain reduction (MD = 1.01 NPRS points, 95% CI: 0.61–1.41), dynamic balance (MD = 5.73 cm, 95% CI: 4.31–7.15), and hop performance (MD = 35.84 mm, 95% CI: 16.84–54.85). Conclusion Dynamic proprioceptive training produced greater multidomain functional recovery than conventional strengthening in recreational sprinters with PFPS. Incorporating sensorimotor and perturbation-based exercises into rehabilitation programmes may improve functional recovery, limb symmetry, and sport-specific performance in athletic populations.